THE EFFECT OF MURROTAL MUSIC THERAPY OF THE QUR'AN ON ANXIETY OF PRE OPERATIONAL SECTION CAESARIAN PATIENTS - Melia Pebrina; Emira Apriyeni; Era Vivi Yanti; Fenny Fernando (Stikes Syedza Saintika Padang, 2022)
According to Riskesdas data, the prevalence of sectio caesarea in Indonesia was 17.6% in 2018. Before sectio caesarea was performed, 90% of preoperative patients had the potential to experience anxiety. One of the non-pharmacological actions in reducing the anxiety of preoperative caesarean section mothers is to listen to the murotal Al-Qur'an. This study aims to examine the effect of murrotal al-qur'an music therapy on the anxiety of preoperative sectiocesarean patients in the Midwifery Room of Mayjen H. A. Thalib Kerinci Hospital in 2021. The type of research was pre-experimental with a One-group pretest and post-test design approach which was carried out from February to February. July 2021. The population of all sectio caesarea patients in 2021 is 149 patients with a purposive sampling technique of 16 people. Data collection using the DASS questionnaire and observation sheets. The data were processed computerized by univariate analysis using descriptive statistics and bivariate analysis using the t-test dependent with a significance level of = 0.05. The results obtained that the average level of anxiety of postoperative caesarean section patients (pretest) was 15.44 and decreased after being given murrotal Al-Qur'an music therapy was 10.75. sectio caesarea(p = 0.000). The results of the study concluded that there was an effect of murrotal Al-Qur'an music therapy on the anxiety of preoperative sectio caesarea patients, it is hoped that this study can be a reference and alternative that can be applied in overcoming anxiety non-pharmacologically in preoperative patients.